Laclau and Mouffe's Radical Hegemony and Democracy Thought: The Transformation of the Free Aceh Movement into the Aceh Party - Anandita Azzahra; Cinta Rasullillah; Davina Shafa Andira; Jihan Rahmadani; Aniqotul Ummah (Universitas Warmadewa, 2024)
The Free Aceh Movement (GAM) is a group that demands that the central government be part of a democracy. The group moved freely and radically with the aim of separating itself from the rest of Indonesia. The focus of this paper is on analyzing GAM's transformation into the Aceh Party, which is different from other radical movements in Indonesia. The purpose of this research is to understand the transformation through Laclau and Mouffe's ideas on radical hegemony and democracy. Radical democracy is a form of struggle in achieving autonomous authority on the basis of equality and equality. The author will use qualitative methods with literature study data collection techniques to strengthen problem analysis. The research results show that GAM is considered radical as it is in line with Laclau and Mouffe's ideas. They form a group to demand certain interests so as to create a state of antagonism and hegemony struggle. The formation of the Aceh Party is inseparable from a long journey to fight for the demands of the community and as a form of building political power in accordance with the environmental conditions of society in Aceh. Currently, the Aceh Party no longer implements radical democracy as it used to do with GAM.